Recurrent Intrahepatic Cholangiocarcinoma – Review - Bekki, Yuki; Von Ahrens, Dagny; Takahashi, Hideo; Schwartz, Myron; Gunasekaran, Ganesh (Frontiers in Oncology, 2021)
Intrahepatic cholangiocarcinoma (ICC) is the second-most common primary liver malignancy after hepatocellular carcinoma. While surgical resection with negative margin is the only curative treatment, ICC has very high rate of recurrence, up to 60-70% after curative resection. We reviewed the current data available on risk factors for ICC recurrence, recurrence pattern (location and timing), treatment options, and future directions. The risk factors for recurrence include elevated preoperative CA19-9, presence of liver cirrhosis, nodal metastasis, positive margins, and vascular invasion. Understanding different recurrence patterns, timing course, and risk factors for early recurrence is important to tailor postoperative surveillance and select treatment strategies including systemic or locoregional therapy. Re-resection can be considered for a selected patient population at experienced centers, and can yield long-term survival. ICC remains a dismal disease given the high likelihood of recurrence. Advances in our understanding of the genomic landscape of ICC are beginning to identify targetable alterations in ICC in subsets of patients that allow for personalized treatment.